Percepetan Tindak Lanjut TORA yang berasal dari Pelepasan Kawasan Hutan untuk Potensi Asset dan Access Reform di Provinsi Kepulauan Riau - Doni Prasetyoadi; Helmya Hilda Putri Fatima (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Follow-up on Land Objects for Agrarian Reform (TORA) is the government's venture to ensure that agrarian reform is by the national target, appropriate with the National Medium Term Development Plan (RPJMN) 2020 – 2024 and provides a real positive impact on society. The aim of accelerating TORA follow-up in the Riau Islands Province is to relieve existing obstacles in implementing agrarian reform and land distribution so the utilization will be fairer. The Structuring and Empowerment Division of the Riau Islands Province National Land Agency Regional Office has the idea of accelerating TORA follow-up by processing TORA data which is superimposed with data resulting from IP4T activities from 2020-2024; obtaining field data through P4T data collection at TORA locations that have not been certified and have never carried out IP4T activities; and obtaining data on potential asset legalization and potential access to reform that can be developed to support community welfare. The results will be discussed by relevant stakeholders to produce spatial information on potential asset legalization that will be carried out in the future, information on potential community land empowerment activities in the area of forest release, and actions that can be implemented to support Agrarian Reform activities.